(untitled) - Moore, Thomas Geoffrey (Cambridge, U.K., 2002)
Moore presents detailed case studies of textiles and shipbuilding to examine the impact of varying degrees of economic openness in the world trading system on the reform, restructuring, and rationalization of Chinese industries. As the book amply demonstrates, the international environment most propitious for change in China's textile and shipbuilding industries during the 1980s and 1990s was one marked by moderate economic closure rather then the ideal-typic economic openness assumed by most observers. Moore also challenges popular notions of China's recent economic success by arguing that Beijing's ability to pursue strategic industrial policy is actually quite limited.
Keywords: Industries,Economic history,Công nghiệp,Lịch sử kinh tế; 1945-,1945-; China,Trung Quốc